RESEARCH ON THE INTEGRATION OF METHODS AND WORK METHODS IN THE PROCESS OF TECHNOLOGICAL EDUCATION IN THE EDUCATION SYSTEM - Shadiyeva, Shahnoza (Журнал иностранных языков и лингвистики, 2023)
Our article examines the relevance of the development of general polytechnic work skills in students for the integration of techniques and operations into the process of technological education in the system of additional education. The operations and techniques of the technological process and their combination are analyzed.